2021
DOI: 10.1021/jacs.0c13178
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazine Detection during Ammonia Electro-oxidation Using an Aggregation-Induced Emission Dye

Abstract: Ammonia electro-oxidation is an extremely significant reaction with regards to the nitrogen cycle, hydrogen economy, and wastewater remediation. The design of efficient electrocatalysts for use in the ammonia electro-oxidation reaction (AOR) requires comprehensive understanding of the mechanism and intermediates involved. In this study, aggregation-induced emission (AIE), a robust fluorescence sensing platform, is employed for the sensitive and qualitative detection of hydrazine (N 2 H 4 ), one of the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…De Vooys et al [38] investigated the chemisorbates formed by eAOR on Au and Pd surfaces using SERS, and they found the existence of N ads as a poisoning species, which supports the G-M mechanism. The presence of hydrazine (N 2 H 4 ), which is one of the important species during eAOR, was detected by aggregation-induced emission [43]. It was confirmed that hydrazine acts as the active intermediate and leads to N 2 formation.…”
Section: Reviewsmentioning
confidence: 80%
“…De Vooys et al [38] investigated the chemisorbates formed by eAOR on Au and Pd surfaces using SERS, and they found the existence of N ads as a poisoning species, which supports the G-M mechanism. The presence of hydrazine (N 2 H 4 ), which is one of the important species during eAOR, was detected by aggregation-induced emission [43]. It was confirmed that hydrazine acts as the active intermediate and leads to N 2 formation.…”
Section: Reviewsmentioning
confidence: 80%
“…When −CHO was replaced by CN, the molecular motion constraints were lifted, resulting in fluorescence quenching. L24 can act as sensor to detect N 2 H 4 in AORs which use commercial Pt/C as an electrocatalyst …”
Section: Detection Of Nitrogen-containing Compoundsmentioning
confidence: 99%
“…Especially in the solid state, this has greatly solved the compatibility problem between the illuminator and the biological medium in the ECL sensor, and effectively reduced the background interference simultaneously and, as a result, it has significantly enhanced the detection sensitivity. 31 Afterwards, more probes with the AIECL property in ECL sensors have been reported, and huge potential and broad application prospects are expected.…”
Section: Introductionmentioning
confidence: 99%